Evaluasi Efektivitas Pelayanan Keperawatan di Puskesmas Beru Beru Desa Beru Beru Kecamatan Kalukku Kabupaten Mamuju Sulawesi Barat - R, Rubiah (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Nursing services are an integral part of the primary health care system provided by community health centers (Puskesmas). The success of these services is not only measured by the number of patient visits but also by the quality of nurse-patient interactions, adherence to standard operating procedures, and clinical outcomes achieved. The Ber-Beru Puskesmas in Kalukku Subdistrict, Mamuju Regency, is one of the Puskesmas serving rural communities with geographical challenges and limited resources. Objective: This study aims to evaluate the effectiveness of nursing services at the Ber-Beru Community Health Center through a multi-indicator approach, namely patient satisfaction, compliance with Standard Operating Procedures (SOPs), and clinical outcomes. Method: This study used a quantitative descriptive design with a cross-sectional approach. The sample consisted of 100 patients selected through purposive sampling. Data were collected through patient satisfaction questionnaires, observations of nurses' compliance with SOPs, and reviews of clinical outcomes from medical records. Data analysis used descriptive statistics and Spearman's correlation test. Results: Patient satisfaction with nursing care was high (average score of 4.2 on a 5-point scale). Nurse compliance with SOPs reached 88%, indicating good implementation of procedures. Clinical results showed that 75% of patients experienced improvement in their condition. Correlation tests showed a positive and significant relationship between SOP compliance and patient satisfaction (ρ=0.65; p<0.01), as well as between patient satisfaction and clinical outcomes (ρ=0.52; p<0.01). Discussion: These findings indicate that nursing services at the Ber-Beru Community Health Center are quite effective, particularly in terms of nurse-patient interaction and SOP implementation. However, there are still challenges in achieving optimal clinical outcomes, particularly due to limitations in resources and supporting facilities. This means that although nurses have worked according to procedures and patients are satisfied, the effectiveness of the service has not been fully reflected in patient recovery outcomes. This highlights the importance of synergy between healthcare staff competence, availability of facilities and infrastructure, and quality management systems for service delivery. Conclusion: Nursing services at the Ber-Beru Community Health Center have demonstrated sufficient effectiveness, but still require improvement, particularly in terms of clinical outcomes and the provision of supporting facilities. Regular evaluations and a systemic approach are essential to maintain the quality of nursing services at rural community health centers.